Study on the Adverse Drug Reactions and Drug-Drug Interactions in Elderly Polypharmacy Patients - Bharti, Vinita; Katiyar, Devendra Kumar (Journal of Neonatal Surgery, 2025)
Aim: This study aims to evaluate the prevalence, severity, and clinical impact of adverse drug reactions (ADRs) and drug-drug interactions (DDIs) in elderly patients receiving polypharmacy (≥5 medications). It also seeks to identify the most commonly implicated drug classes and assess the association between polypharmacy, comorbidities, and medication-related complications. Materials and Methods: A prospective observational study was conducted at a tertiary care hospital, including 100 elderly patients (≥65 years) on multiple medications. Data on demographics, comorbidities, medication history, ADRs, and DDIs were collected using a structured format. ADRs were assessed for causality (Naranjo Scale), severity (Hartwig and Siegel Scale), and preventability (Schumock and Thornton criteria). DDIs were identified and classified based on their clinical significance using standard drug interaction databases. Statistical analysis was performed using SPSS 25.0, with significance set at p < 0.05. Results: The mean age of the patients was 72.5 ± 5.8 years, with 55% males and 45% females. The average number of comorbidities was 3.2 ± 1.5, with hypertension (65%), diabetes mellitus (50%), and ischemic heart disease (25%) being the most prevalent. Polypharmacy was observed in all patients, with 40% taking 5-6 medications, 30% on 7-8, and 10% on more than 10 drugs. ADRs were recorded in 50% of patients, with 40% classified as probable and 20% as definite ADRs. Severe ADRs were noted in 20% of cases (p=0.01). Moderate-to-severe DDIs were identified in 75% of patients, leading to hospitalization in 15% of cases (p=0.02) and medication changes in 40% (p=0.03). The most implicated drug classes in ADRs and DDIs included antihypertensives (30% ADRs, 25% DDIs), antidiabetics (25% ADRs, 20% DDIs), NSAIDs (15% ADRs, 30% DDIs), and anticoagulants (20% ADRs, 35% DDIs, p=0.005). Conclusion: This study highlights the high prevalence of ADRs and DDIs in elderly polypharmacy patients, with moderate-to-severe ADRs affecting 50% of patients and hospitalization occurring in 15% of DDI cases. Polypharmacy significantly increased the risk of ADRs and DDIs, particularly with high-risk medications such as antihypertensives, anticoagulants, NSAIDs, and antidiabetics. The findings emphasize the need for regular medication reviews, deprescribing strategies, and improved pharmacovigilance to minimize medication-related harm in geriatric patients